ANALISIS DAMPAK TEKNOLOGI ARTIFICIAL INTELLEGENCE (AI) TERHADAP PEMBELAJARAN ADAPTIF PADA PELAJAR MUDA - Saryani Saryani; Irawan Irawan; Ali Murtado; Riki Hidayat; Ikhsan Abi Maulana; Vira Destiaji (Universitas Tangerang Raya, 2025)
The use of intelligent systems in education is increasingly being utilized to support learning processes that adapt to individual student needs. The adaptive learning approach is one application of Artificial Intelligence (AI) technology that aims to improve the effectiveness and quality of learning, particularly for young learners. This study was conducted to examine the impact of the application of artificial intelligence (AI) technology on adaptive learning in young learners. The research employed a quantitative descriptive approach, with data collection conducted through a quantitative analysis using percentage techniques to illustrate the trends in respondents' perceptions. The results showed that AI-based adaptive learning improved material comprehension, improved learning time efficiency, and improved student engagement in the learning process. However, challenges were identified, including limited digital literacy and potential dependency on technology. In conclusion, AI technology makes a positive contribution to supporting adaptive learning in young learners. However, its use requires careful monitoring and the active role of educators to ensure optimal learning outcomes.